RELATIONSHIP BETWEEN CLINICAL FINDINGS OF CARPAL TUNNEL SYNDROME WITH ENMG AND USG WRIST RESULT - Masruroh Rahayu; Shahdevi Nandar Kurniawan; Neila Raisa; Farida Widyastuti (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2022)
Background: Carpal tunnel syndrome is symptomatic compression neuropathy of median nerve in carpal tunnel on wrist causes functional decreased in that area. CTS is diagnosed from clinical, physical examination, also from ENMG and USG wrist. This research aims to know about CTS characteristics and the relationship between clinical findings of CTS with ENMG and USG wrist results. Objective: This study aims to determine whether there is a relationship between the clinical findings of patients diagnosed with CTS and the results of ENMG and wrist ultrasound at the Neurology Polyclinic of Saiful Anwar Hospital, Malang. Methods: This research was descriptive observational. Data were collected from anamnesis and physical examination at Neurology Polyclinic Saiful Anwar Malang Hospital (RSSA) from April to December 2017, then examined by ENMG and USG wrist at RSSA. There are 27 patients suspected of CTS who meet inclusion and exclusion criteria. Results: From 9 months (April-December 2017) found 27 patients suspected CTS, about 19 patients (70,37%) were female and 7 patients (19,63%) were male. The majority of the age group is 25-65 years old (66,67%). Most of the occupations were housewives (48,15%). Patients most came with chief complaint of tingling (88,89%) with positive tinnel sign (77,78%), and most concomitant diseases were hypertension (48,15%). The ENMG results confirmed CTS about 92,59%, compared to the USG that confirmed CTS about 85,19%. Statistical analysis with Pearson Chi-Square test showed no relationship between clinical findings of CTS (Tinnel, Phalen, Counter Phalen, Flick test) with ENMG and USG wrist results. Conclusion: This research concluded no relationship between clinical findings of CTS with ENMG and USG wrist results.